Sick/not sick : a guide to rapid patient assessment - Helbock, Mike.; Jerin, John M. (Sudbury, Massachusetts : Jone and Bartlett Learning, 2011)
Completely updated with new case studies throughout, Sick/Not Sick, Second Edition is designed to help EMS personnel develop rapid patient assessment skills. This resource distills years of field experience into a workable formula that both inexperienced and experienced providers can use.Sick/Not Sick teaches EMS personnel how to quickly collect information and discern what details are important in order to provide immediate initial care. After all, in EMS it comes down to whether the patient is Sick or Not Sick. --Book Jacket.
Why sick/not sick? -- Sick/not sick in a nutshell -- Sick/not sick starts while en route -- The clinical picture of a medical patient -- The clinical picture for a trauma patient -- Make a decision -- What if I make the wrong decision? -- Common mistakes -- Pediatric sick/not sick in a nutshell -- The pediatric triangle -- Pediatrics : make a decision -- Medical case studies -- Trauma case studies -- Pediatric case studies.
Includes index.
Keywords: EMERGENCY MEDICAL SERVICES -- HANDBOOKS, MANUALS, ETC